Pengembangan Aplikasi Website Pemasaran Villa di Desa Ungasan - Muhamad Hidayat; Anak Agung Istri Ngurah Eka Karyawati; Gusti Ayu Vida Mastrika Giri (Jurnal Pengabdian Informatika, 2025)
The development of a villa marketing website in Ungasan, Bali, aims to utilize digital technology to enhance tourism and local economic potential. The website is designed to facilitate villa owners in promoting their properties widely by providing features such as booking systems, online payments, and villa data management. The implementation results are expected to enable the website to provide easy access for potential renters and increase the efficiency of property management. This development is expected to contribute to the digitalization of marketing in the local tourism sector.